2020
DOI: 10.1186/s12884-020-2739-z
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare worker knowledge and skills following coaching in WHO early essential newborn care program in the Solomon Islands: a prospective multi-site cohort study

Abstract: Background Newborn mortality in Oceania declined slower than other regions in the past 25 years. The World Health Organization (WHO) introduced the Early Essential Newborn Care program (EENC) in 2015 in Solomon Islands, a Small Island Developing State, to address high newborn mortality. We explored knowledge and skills retention among healthcare workers following EENC coaching. Methods Between March 2015 and December 2017, healthcare workers in fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
2
8
0
Order By: Relevance
“…The Pacific low- and middle-income countries had taken actions to improve to improve the quality of maternal and newborn care over the past decades, including improvements of health infrastructure, considerable financial investment, and training program of healthcare workers [ 48 ]. Several island countries launched the Early Essential Newborn Care program (EENC) introduced from the WHO [ 49 ]. Meanwhile, the international medical program [ 50 ], and the reproductive health study [ 51 ] probably promoted trends of neonatal disorders declined pronouncedly in Cook Islands.…”
Section: Discussionmentioning
confidence: 99%
“…The Pacific low- and middle-income countries had taken actions to improve to improve the quality of maternal and newborn care over the past decades, including improvements of health infrastructure, considerable financial investment, and training program of healthcare workers [ 48 ]. Several island countries launched the Early Essential Newborn Care program (EENC) introduced from the WHO [ 49 ]. Meanwhile, the international medical program [ 50 ], and the reproductive health study [ 51 ] probably promoted trends of neonatal disorders declined pronouncedly in Cook Islands.…”
Section: Discussionmentioning
confidence: 99%
“…After training, there was a significant increase in knowledge and skills and a final score of correct answers above 84%, as expected (and suggested) in AHA training, a world reference in CPR training. In a similar way, research has shown an increase of 20.4% to 20.9% ( 14 ) , 28% ( 11 ) , 45% ( 15 ) , in theoretical knowledge after training. Regarding skills, there was a percentage of correct answers of 81.5% ( 16 ) and up to 95% ( 15 ) immediately after the educational intervention.…”
Section: Discussionmentioning
confidence: 59%
“…The improvement of the results after T1 in both groups con rms the literature data that demonstrate the importance of training to improve CPR skills. This improvement happens due to intervention and is independent of the group being trained, because studies involving laypeople [19], students [20] and health professionals [21] also observed knowledge superior to the initial one. A study with nurses showed a signi cant increase in the average level of knowledge and practice after a formal training program [22].…”
Section: Discussionmentioning
confidence: 99%